Optimization of Rice Supply Chain Traceability Using Blockchain: A Case Study in Bekasi Regency - Agus Barlianto; Irman Hermadi; Sri Wahjuni (Eduvest - Journal of Universal Studies, 2025)
Rice is a staple food in Indonesia, with a high consumption rate of 81.044 kg per capita annually and a production volume of 31.54 million tons in 2022. Ensuring traceability in the rice supply chain is crucial for food quality and safety. However, the industry faces logistical challenges, such as inadequate infrastructure, poor interagency coordination, and unintegrated information systems. At Menata Citra Selaras (MCS), the largest rice milling unit in Bekasi Regency, manual systems hinder decision-making and product traceability. This study aims to optimize traceability by leveraging blockchain technology. We developed Ricetrack, a prototype application based on Sawtooth blockchain technology, to enhance supply chain traceability. The methodology includes identifying actors and user stories, system modeling, design, and prototype testing in an operational environment. Data analysis, both quantitative and qualitative, showed significant improvements in traceability and data transparency, validated through surveys and stakeholder feedback. The study concludes that blockchain technology offers substantial benefits for the rice supply chain, providing added value to all stakeholders and enhancing operational efficiency for MCS and other companies in the Indonesian rice industry.